Programmable CSF Shunt Valves: Radiographic Identification and Interpretation - Lollis, S.S.; Mamourian, A.C.; Vaccaro, T.J.; Duhaime, A.-C. (American Journal of Neuroradiology, 2010)
SUMMARY: The programmable CSF shunt valve has become an important tool in hydrocephalus treatment, particularly in the NPH population and in pediatric patients with complex hydrocephalus. The purpose of this study is to provide a single reference for the identification of programmable shunt valves and the interpretation of programmable shunt valve settings. Four major manufacturers of programmable shunts agreed to participate in this study. Each provided radiographic images and legends for their appropriate interpretation. Issues of MR imaging compatibility for each valve are also discussed. HhighLlowMmediumNPHnormal pressure hydrocephalusP/Lperformance levels